Urgensi Kebijakan Kota Ramah Gender di Tanjungpinang - Abdurrahman Al Haz; Ainul Nurmadiah; Beki Sukmawan (JOURNAL OF ADMINISTRATIVE AND SOCIAL SCIENCE, 2024)
This Based on BPS data, it can be seen that the Gender Empowerment Index in Tanjung Pinang will reach 76.64 in 2021. This figure is quite high and has increased from the previous year. in contrast to the Riau Islands Province's gender empowerment index, which has decreased from 62.02 in 2020 to 58.91 in 2021. This shows that so far, Tanjungpinang is committed to implementing development that guarantees gender equality and justice. The research method uses secondary data. The Tanjungpinang city RPJMD is a research method that uses existing data from the Tanjungpinang city RPJMD document as the main source of information. The data is then analyzed qualitatively to find out whether the RPJMD of Tanjungpinang City has paid attention to gender aspects in its planning. Data collection techniques in this method include document studies and content analysis.